2022
DOI: 10.1128/mbio.03196-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Borderline Oxacillin-Resistant Staphylococcus aureus Detected during a Pseudo-outbreak of Methicillin-Resistant S. aureus in a Neonatal Intensive Care Unit

Abstract: In this study, we found a high prevalence of Staphylococcus aureus isolates exhibiting a borderline oxacillin resistance phenotype (BORSA) in our neonatal intensive care unit (NICU) serendipitously due to the type of MRSA screening agar used by our laboratory for active surveillance cultures. Subsequent phenotypic and molecular characterization highlighted an unexpected prevalence and variability of BORSA isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Notably, the latter represents an improvement of the former with higher statistical power. The ability of BratNextGen to reveal ancestral recombination has been applied in studies related to Streptomyces species [ 79 ], antibiotic-resistant Staphylococcus aureus strains [ 80 ], and differentiated Xylella fastidiosa isolates [ 81 ].…”
Section: Current Bioinformatics Tools For Recombination Analysismentioning
confidence: 99%
“…Notably, the latter represents an improvement of the former with higher statistical power. The ability of BratNextGen to reveal ancestral recombination has been applied in studies related to Streptomyces species [ 79 ], antibiotic-resistant Staphylococcus aureus strains [ 80 ], and differentiated Xylella fastidiosa isolates [ 81 ].…”
Section: Current Bioinformatics Tools For Recombination Analysismentioning
confidence: 99%
“…While PBP2a has historically been considered the main driver of MRSA, the recent finding that high-level S. aureus β-lactam resistance occurs in strains not capable of producing PBP2a has led to investigation of non-canonical pathway(s) of MRSA development as well as fundamental questions regarding the clinical diagnostic practices that rely on detection of mecA , the gene encoding PBP2a, as a MRSA determinant [ 37 ]. Recent studies have revealed that development of PBP2a-independent MRSA is associated with PBP4 production in community-acquired MRSA isolates and/or overproduction of a PBP4 variant within the hospital-acquired strain COL background.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was isolated from cell-suspensions and sequenced as previously described 23 , 63 . Briefly, DNA was quantified with Quant-iT PicoGreen dsDNA assay (Thermo Fisher Scientific, Waltham, MA, USA), with 0.5 ng used as input for Illumina Nextera XT library preparation (Illumina, San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…WGS has enabled comparative genomics studies that have provided foundational knowledge of S. pseudintermedius populations and pathologies 20 , 21 . Similar to S. aureus , S. pseudintermedius has an open pangenome; most accessory genes are lineage- or strain-specific 20 – 23 , and antibiotic resistance gene (ARG) content and virulence factor repertoires vary by multilocus sequence type (MLST) 20 , 24 . Additional studies have characterized S. pseudintermedius genome content by geographic isolation 21 , host-species for clinical isolates 22 , niche-type for veterinary isolates 20 , 25 , and mecA presence 26 .…”
Section: Introductionmentioning
confidence: 99%